Detection and Sensing of Mines, Explosive Objects, and Obscured Targets XXIV 2019
DOI: 10.1117/12.2519484
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of possibilistic fuzzy local information C-means and possibilistic K-nearest neighbors for synthetic aperture sonar image segmentation

Abstract: Synthetic aperture sonar (SAS) imagery can generate high resolution images of the seafloor. Thus, segmentation algorithms can be used to partition the images into different seafloor environments. In this paper, we compare two possibilistic segmentation approaches. Possibilistic approaches allow for the ability to detect novel or outlier environments as well as well known classes. The Possibilistic Fuzzy Local Information C-Means (PFLICM) algorithm has been previously applied to segment SAS imagery. Additionall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Recent research on SSS target recognition has shown that the target recognition method based on CNNs has outperformed traditional machine learning methods, including the fuzzy logic method, K nearest neighbor, support vector machines, etc., [15][16][17]. With an increasing scale, the recognition network can extract deeper features from images to obtain richer feature information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent research on SSS target recognition has shown that the target recognition method based on CNNs has outperformed traditional machine learning methods, including the fuzzy logic method, K nearest neighbor, support vector machines, etc., [15][16][17]. With an increasing scale, the recognition network can extract deeper features from images to obtain richer feature information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Descriptions of the seafloor are critical for many applications, especially mine countermeasures where awareness of environmental changes improves mine detection [1]. Many scene understanding methods for SAS have been developed which rely upon superpixel segmentations [2,3]. While metrics have been implemented to score superpixel oversegmentations in reference to crisp ground truth [4], we develop a labeling scheme and scoring metric designed for imagery with soft boundaries and complex transitions between textures and compare our approach to traditional crisp methods.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome those deficits in pixel clustering procedure, we adopt Possibilistic C-Means (PCM) clustering strategy. PCM has long history of theoretical background [22,23] and many successful applications in engineering [24,25] and medical domain [26,27] and many constraint relaxed models exist [28]. We also relax some part of standard PCM as proposed in [22] to adapt the domain constraints and due to the low intensity contrast between the target area and the background, we need fuzzy stretching [2] to enhance the contrast.…”
Section: Introductionmentioning
confidence: 99%